Religious Involvement and Self-Perceived Spiritual Health: A Quantitative Study of Canadian Children with Disabilities. (1st October 2020) - Michaelson, Valerie; Swinton, John; King, Nathan; Pickett, William
Abstract: This study presents a national analysis of 24, 190 young Canadians in which relationships between religious group involvement and the spiritual health of children with and without disabilities is described. Two key findings emerged: 1) Children who report religious involvement report higher self-rated importance of spiritual health compared with non-involved peers; 2) among involved children, spiritual health was rated as less important among three groups of young people in particular: those with multiple disabilities, those with a learning exceptionality and those with behavioural disorders. Implications for inclusive ministry are discussed.